Development of Project Assessment Instruments to Assess Mathematical Problem Solving Skills on A Project-Based Learning - Wahyuni, Vera; Kartono, Kartono; Susiloningsih, Endang (Journal of Research and Educational Research Evaluation, 2018)
Assessment of the results of the study were not able to use the technique only tests the need for an assessment that can assess the 3 aspects of cognitive, affective and namely psychomotor assessment authentic like i.e. assessment of the project. Troubleshooting is the ability that must be mastered in maths learning then perlua the existence of an appropriate assessment that can assess the mathematical problem solving skills. This research aims to develop assessment instrument project to assess mathematical solving skills on a project-based learning that is valid, reliability and practical use. The type of research used in this research is the research development (research and development) with the model of the development of nontes. The subject of a trial that is grade VIII SMP Negeri Semarang 40. The data in the research gained from the results of the test of the validity, reliability and practicality. The research results showed that the assessment instrument project to assess mathematical problem solving skills on a project-based learning is declared invalid based on the input of experts and of the results obtained from the calculation of the ICC retrieved r_xx > 0,814 reliability, validity of the results invalid constructs on a small scale have the goodness of fit index 0,942 > 0.90 and massive scale have index goodness of fit 0.935 > 0.90 reliability then both showed 0,848 > 0.7 on a small scale and 0867 > 0.7 on a massive scale, as well as meet the criteria of the practical meaning of the instrument indicates the assessment of the project to assess mathematical problem solving skills in project based-learning that have been developed in valid, reliabil and practical use as well as proven to be used to assess mathematical problem solving skills of students of JUNIOR HIGH SCHOOL. This research is expected to be later exploited and used as a reference in the learning of mathematics. Kata Kunci: Penilaian Proyek, Keterampilan Pemecahan Masalah, Project Based -Learning